Pemetaan Strategi E-Bisnis Untuk Meningkatkan Daya Saing Perusahaan - Anugerah, Ary Taruna (Syntax Corporation, 2025)
In the era of globalization and advances in information technology, companies must leverage e-business strategies to remain competitive in an increasingly tight market. This study aims to map effective e-business strategies to enhance corporate competitiveness. The research employs qualitative and quantitative methods with a descriptive design, involving interviews with company executives and e-business managers and distributing questionnaires to employees implementing e-business strategies. The findings reveal that applying e-business strategies, including artificial intelligence technology and supply chain integration, significantly improves operational efficiency and customer experience. Furthermore, companies that adopt holistic and integrated e-business strategies are better positioned to adapt to market changes and meet customer expectations. The implications of this research highlight the need for companies to design and implement e-business strategies that encompass information security aspects and employee engagement to enhance their competitiveness in the continuously evolving digital era. Thus, this research provides important insights for companies in optimizing their e-business strategies.